Doctor Faustus; the life of the German composer, Adrian Leverkuhn - Mann, Thomas, 1875-1955; Lowe-Porter, H. T. 1876-1963 (Helen Tracy) (New York, A. A. Knopf, 1948)
A pseudo-biography which recounts the tragic life of Adrian Leverkhuhn who sells his soul to the devil for twenty-four years of musical genius.
Keywords: Composers -- Fiction; Genius -- Fiction